Unpacking the Role of Instructional Leadership in Teacher Professional Development - Osias Kit T Kilag; John Michael Sasan (Advanced Qualitative Research, 2023)
This qualitative study aimed to unpack the role of instructional leadership in teacher professional development. Ten teachers and three coordinators from PAU Excellencia Global Academy Foundation, Inc. participated in the study. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed three main themes. First, instructional leadership practices were found to be critical in promoting teacher learning and development. The participants emphasized the importance of leaders modeling effective teaching practices, providing feedback, and facilitating collaboration and learning opportunities. Second, the study showed that the quality of teacher-administrator relationships was essential in promoting teacher professional growth. The participants highlighted the significance of trust, open communication, and mutual respect in building positive relationships. Lastly, the study revealed that teacher professional development is a continuous and ongoing process that requires sustained support from school leaders. The participants emphasized the need for ongoing professional development opportunities, such as workshops, mentoring, and coaching. These findings have important implications for educational leaders and policy-makers in promoting effective teacher professional development. School leaders should prioritize instructional leadership practices that model effective teaching practices and facilitate collaborative learning opportunities. They should also foster positive teacher-administrator relationships and provide ongoing professional development opportunities to support teachers in their professional growth. By doing so, they can promote a culture of continuous learning and development in their schools, ultimately leading to improved student learning outcomes.